Gut Microbes Reveal Pseudomonas Medicates Ingestion Preference via Protein Utilization and Cellular Homeostasis Under Feed Domestication in Freshwater Drum, Aplodinotus grunniens - Song, Changyou; Wen, Haibo; Liu, Guangxiang; Ma, Xueyan; Lv, Guohua; Wu, Ningyuan; Chen, Jianxiang; Xue, Miaomiao; Li, Hongxia; Xu, Pao (Frontiers in Microbiology, 2022)
With strong demand for aquatic products, as well as a rapid decrease in global fishery resources and capture fisheries, domesticating animals to provide more high-quality proteins is meaningful for humans. Freshwater drum (Aplodinotus grunniens) is widely distributed in the wild habitats of North America. However, the research on A. grunniens and the feed domestication with diets composed of artificial compounds remains unclear. In this study, a 4-month feeding domestication experiment was conducted with A. grunniens larvae to evaluate the underlying mechanism and molecular targets responsible for alternations in the ingestion performance. The results indicated that a significant increase in the final body weight was exhibited by the feed domesticated group (DOM, 114.8 g) when compared to the group that did not ingest the feed (WT, 5.3 g) as the latest version we raised From the result, the final body weight exhibited significant increase between unfavorable with the feed (WT, 5.3 g) and feed domesticated group (DOM, 114.8 g). In addition, the enzyme activity of digestive enzymes like amylase, lipase, and trypsin was increased in DOM. Genes related to appetite and perception, such as NPY4R, PYY, and LEPR, were activated in DOM. 16s rRNA gene sequencing analysis revealed that Pseudomonas sp. increased from 58.74% to 89.77% in DOM, which accounts for the dominant upregulated microbial community at the genus level, followed by Plesiomonas. Analogously, Mycobacterium, Methylocystis, and Romboutsia also accounted for the down-regulated microbes in the diversity. Transcriptome and RT-PCR analysis revealed that feed domestication significantly improved protein digestion and absorption, inhibited apoptosis by AGE-RAGE signaling, and activated extracellular matrix remodeling by relaxin signaling. Integrated analysis of the microbiome and host transcriptome revealed that Pseudomonas-mediated ingestion capacity, protein utilization, and cellular homeostasis might be the underlying mechanism under feed domestication. These results indicate Pseudomonas and its key genes relating to food ingestion and digestion could serve as the molecular targets for feed domestication and sustainable development in A. grunniens.